Inovasi produk diaper bag sebagai solusi privasi untuk kebutuhan bayi di ruang publik - Faqih, Izzul; Prasetya, Rahmawan Dwi; Adita, Sekar (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
The growing modern lifestyle has created a new habit for parents, which is traveling such as traveling with their baby. However, this situation presents various challenges, especially in meeting the needs of the baby. To accommodate these needs, parents often use conventional baby bags that are considered less effective because the compartments are not well organized, which can make it difficult for parents when they have to change diapers immediately. Given the high frequency of urination in infants, it is very important to change diapers regularly to prevent rashes. In public spaces such as Malioboro tourist area, which lacks mother and baby room facilities, parents often have difficulty finding a place with adequate privacy to change diapers. This situation forces them to look for a special space (nursery room) that may be far from their location. This design uses the design thinking method to understand user needs. Based on the results of the data analysis that has been carried out, a diaper bag product design is needed that has an organized compartment arrangement and a means to change baby diapers in the form of a mat equipped with a privacy cover feature. This research resulted in 5 variants of diaper bag products with the main characteristic of creating privacy in public spaces that lack facilities when changing baby diapers.